2020
DOI: 10.1186/s13054-020-2773-2
|View full text |Cite
|
Sign up to set email alerts
|

The global survival rate among adult out-of-hospital cardiac arrest patients who received cardiopulmonary resuscitation: a systematic review and meta-analysis

Abstract: Background: To quantitatively summarize the available epidemiological evidence on the survival rate of out-ofhospital cardiac arrest (OHCA) patients who received cardiopulmonary resuscitation (CPR). Methods: We systematically searched the PubMed, Embase, and Web of Science databases, and the references of retrieved articles were manually reviewed to identify studies reporting the outcome of OHCA patients who received CPR. The overall incidence and outcome of OHCA were assessed using a random-effects meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
328
3
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(405 citation statements)
references
References 30 publications
7
328
3
22
Order By: Relevance
“…6 A systematic review & meta-analysis by Yan et al showed that prehospital stage was the most impactful stage for care of OHCA patients and where efficient CPR from EMS translated to highest incidence of ROSC (36.3%; 95% CI 23.8 -48.9%). 7 This emphasizes the need to educate the community regarding the importance of using an ambulance and EMS systems, so that earlier AED use and ACLS interventions can be administered. 8 Continuing with the quality of the EMS services available to our patient group only 7.8% received CPR, with only 12.5% of ambulances having Basic Life Support (BLS) trained personnel.…”
Section: Discussionmentioning
confidence: 99%
“…6 A systematic review & meta-analysis by Yan et al showed that prehospital stage was the most impactful stage for care of OHCA patients and where efficient CPR from EMS translated to highest incidence of ROSC (36.3%; 95% CI 23.8 -48.9%). 7 This emphasizes the need to educate the community regarding the importance of using an ambulance and EMS systems, so that earlier AED use and ACLS interventions can be administered. 8 Continuing with the quality of the EMS services available to our patient group only 7.8% received CPR, with only 12.5% of ambulances having Basic Life Support (BLS) trained personnel.…”
Section: Discussionmentioning
confidence: 99%
“…The 1-year global survival rates are ≈7.7% and increase to 12.6% among patients receiving bystander cardiopulmonary resuscitation (CPR). 1 Early initiation of effective compressions with minimal interruptions is essential to maximizing favorable outcomes after out-of-hospital cardiac arrest. In addition, the use of mechanical CPR in resource-limited efforts with prolonged transportation time should still be promoted as a means to support emergency medical services out-of-hospital care.…”
Section: Finding the Right Pace: Addressing The Transition From Manuamentioning
confidence: 99%
“…Despite these efforts, the one-year survival rate is 13% for individuals who experience IHCA and 7% for OHCA. 5,6 Furthermore, the majority of survivors report physical disabilities, cognitive impairment or mental illness, potentially contributing to the decreased quality of life commonly reported post-arrest. [7][8][9] Advanced knowledge of patient prognosis following a cardiac arrest is necessary to determine if resuscitation efforts are futile and ensure value-congruent care.…”
Section: Introductionmentioning
confidence: 99%